Fortunes of Dragons: Cohort size effects on life outcomes. (4th May 2021) - Agarwal, Sumit; Qian, Wenlan; Sing, Tien Foo; Tan, Poh Lin
Abstract : This paper examines the long-term effects of birth cohort size on life outcomes. Using administrative data from Singapore, we study the outcomes of large birth cohorts created by the Chinese superstitious practice of zodiac birth timing, where parents prefer to give birth in the year of the Dragon. This practice is followed exclusively by the Chinese majority, with no similar patterns detected among non-Chinese minorities, allowing us to differentiate cohort size effects from confounding year-of-birth effects. Despite government efforts to increase public educational resources for these cohorts, Chinese Dragons earn lower incomes and are less likely to gain admission to national universities. There is also evidence of negative externalities on non-practising populations who happen to enter the labour market at the same time as Chinese Dragons. Our analysis suggests that the adverse life outcomes are not due to selection, but rather reflect the aggregate resource implications of birth cohort size. Supplementary material is available for this article at: https://doi.org/10.1080/00324728.2020.1864458